2010
DOI: 10.1590/s1807-59322010000900014
|View full text |Cite
|
Sign up to set email alerts
|

Difficult-to-control asthma management through the use of a specific protocol

Abstract: The present study is a critical review of difficult‐to‐control asthma, highlighting the characteristics and severity of the disease. It also presents a protocol for the management of patients with this asthma phenotype. The protocol, which was based on relevant studies in the literature, is described and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 159 publications
0
8
0
4
Order By: Relevance
“…Nowadays asthma treatment for the elderly is mainly limited to pharmacological treatment aimed at controlling the symptoms and bronchial inflammation caused by this disease, while other therapeutic approaches to controlling asthma have been neglected [11,12]. Only a few studies based on physical exercise and breathing training have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays asthma treatment for the elderly is mainly limited to pharmacological treatment aimed at controlling the symptoms and bronchial inflammation caused by this disease, while other therapeutic approaches to controlling asthma have been neglected [11,12]. Only a few studies based on physical exercise and breathing training have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging approach in many centres is to select add‐on therapies according to asthma phenotype (Figure 1, Tables 3,4). 25,26 This approach requires that objective measures of airway inflammation be applied.…”
Section: Establishing a Severe Asthma Servicementioning
confidence: 99%
“…(3) In a review article, Giavina-Bianchi et al described the principal characteristics of difficult-to-control asthma and a protocol for its management. (4) Dalcin et al studied the prevalence of controlled asthma, partially controlled asthma, and uncontrolled asthma (56%, 27%, and 17%, respectively) and found that greater asthma severity, limited availability of medications, and no inhaled corticosteroid use were factors associated with poor disease control. (5) In addition, Dalcin & Perin published a review article on the assessment and management of acute asthma in the emergency room.…”
Section: Introductionmentioning
confidence: 99%